Crotonaldehyde hydrogenation on platinum–titanium oxide and platinum–cerium oxide catalysts: selective CO bond hydrogen requires platinum sites beyond the oxide–metal interface. Issue 18 (5th May 2016) - Yang, Xin; Mueanngern, Yutichai; Baker, Quinn A.; Baker, L. Robert
Abstract : We have investigated a series of Pt–TiO2 and Pt–CeO2 catalysts for crotonaldehyde hydrogenation with the goal of better understanding the kinetics of CO bond hydrogenation. Abstract : We have investigated a series of Pt–TiO2 and Pt–CeO2 catalysts for crotonaldehyde hydrogenation with the goal of better understanding the kinetics of CO bond hydrogenation. It has been established that in these systems, Pt is the active phase for CC bond hydrogenation, while the interface between Pt and an active metal oxide is required for selective CO bond hydrogenation. In this work we demonstrate that in addition to the presence of an active oxide–metal interface, there is also a need for accessible Pt sites beyond this interface to facilitate CO bond hydrogenation. Passivating Pt with TiO2 at coverages approaching unity is shown to decrease the rate of CO bond hydrogenation in exact proportion to the rate of CC bond hydrogenation, suggesting that both pathways become rate limited by the accessible Pt surface area at high oxide coverage. A similar kinetic result is demonstrated for CeO2 nanocubes deposited on a Pt film, where the rate of CO bond hydrogenation initially increases with CeO2 nanocube coverage and then decreases again at high CeO2 coverage, even though the nanocubes remain discrete. Because the density of interface sites scales linearly with the coverage of CeO2 nanocubes on the Pt surface, this decrease in activity shows that accessible Pt sites rather than oxide–metal interface sites become rate limiting for CO bond hydrogenation at high oxide coverage. Finally, in bilayer catalysts of CeO2 and Pt nanocubes, we find that both Pt-on-CeO2 and CeO2 -on-Pt are active for CC bond hydrogenation, while only Pt-on-CeO2 is active for CO bond hydrogenation. These results are discussed in terms of a spillover-mediated reaction mechanism in which a reaction intermediate must diffuse either to or across the active oxide–metal interface in order to promote CO bond hydrogenation.